2009
DOI: 10.1128/jcm.01753-08
|View full text |Cite
|
Sign up to set email alerts
|

Abbott RealTime Hepatitis C Virus (HCV) and Roche Cobas AmpliPrep/Cobas TaqMan HCV Assays for Prediction of Sustained Virological Response to Pegylated Interferon and Ribavirin in Chronic Hepatitis C Patients

Abstract: Two commercial real-time PCR assays are currently available for sensitive hepatitis C virus (HCV) RNA quantification: the Abbott RealTime HCV assay (ART) and Roche Cobas AmpliPrep/Cobas TaqMan HCV assay (CAP/CTM). We assessed whether the two real-time PCR assays were more effective than Roche Cobas Amplicor HCV Monitor test, v.2.0 (CAM) for prediction of the sustained virological response (SVR) to pegylated interferon (PEG-IFN) plus ribavirin (RBV) in chronic hepatitis C. Sixty patients chronically infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…Therefore, assays of the HCV RNA load in serum or plasma have become essential for confirming active infections and guiding the initiation and continuation of treatment with pegylated interferon and ribavirin or other antivirals. At present, real-time PCR is the benchmark technique for detecting and quantitating HCV RNA in clinical practice, with limits of detection of 10 to 15 IU/ml (4,7,15). However, these assays require high levels of technical skill and are labor-intensive in routine use.…”
mentioning
confidence: 99%
“…Therefore, assays of the HCV RNA load in serum or plasma have become essential for confirming active infections and guiding the initiation and continuation of treatment with pegylated interferon and ribavirin or other antivirals. At present, real-time PCR is the benchmark technique for detecting and quantitating HCV RNA in clinical practice, with limits of detection of 10 to 15 IU/ml (4,7,15). However, these assays require high levels of technical skill and are labor-intensive in routine use.…”
mentioning
confidence: 99%
“…These results indicate that ART is more useful than CAM for the prediction of SVR when patients have rapid declines of HCV RNA levels during the early phase of treatment. The reasons for this are that ART is an advanced quantitative assay based on the real-time PCR method, it is more sensitive, and has a broader range of determination than conventional methods [20,[27][28][29]. The lower limit of detection of ART is 12 IU/ml and the range of measurement is from 1.08 to 8.0 log IU/ml, but the detection limit of CAM is 500 IU/ml and the range of CAM is 2.7 to 6.7 log IU/ml.…”
Section: Discussionmentioning
confidence: 99%
“…One study examining the potential benefits of real-time versus traditional PCR found higher positive predictive values (PPVs) for subsequent sustained viral response when assessing for undetectable virus at weeks 4 and 12. The combined PPV for sustained viral response for the two real-time PCR assays with undetectable virus at week 12 was 94%, versus only 74% for those with undetectable virus by traditional PCR [24]. An additional assay called transcription-mediated amplification (TMA) is a qualitative test that reports a LLOD as low at 5 IU/mL.…”
Section: Polymerase Chain Reactionmentioning
confidence: 98%